From Inclusion to Leadership: Disabled “Misfitting” in Congregational Ministry - Raffety, Erin (Theology today, 2020)
Drawing on ethnographic research, Scripture, and theology, this article posits that Christian arguments for inclusion with people with disabilities often fail to undermine ideologies of normalcy lurking at the heart of redemption. By reading the healing of blind Bartimaeus (Mark 10:46-52) with the pitfalls of inclusion and current research in mind, I follow theologian Sharon V. Betcher in challenging readers to resist making disabled persons but “plot props” in able-bodied enlightenment, and let Jesus’ ministry direct us to Bartimaeus’ ministry in the text. I argue that in uplifting the faith and leadership of Bartimaeus, Jesus points to Bartimaeus as the protagonist, inviting us to perceive and receive the faithfulness and leadership of people with disabilities in their seeming disruptions and evident differences. In order to aid able-bodied people in apprehending the leadership of persons with disabilities, I draw on Rosemarie Garland-Thomson’s concept of disabled “misfitting,” a feminist materialist notion of disability that emphasizes the importance of context and materiality in disablement. Using the concept of misfitting to analyze ethnographic examples calls attention to the opportunities and possibilities created in disabled people’s leadership and challenges congregations to consider where their paradigms of leadership may still be oriented around ideologies of normalcy and practices of able-bodied inclusion. Indeed, congregations are invited to receive the work of the Spirit in persons with disabilities by entering into dignifying dialogue with new forms of ministry and leadership.